Pelatihan Penulisan Naskah Kata Sambutan Bagi Pengajian Remaja Nurussalam Aek Badak - Nur - Afifah (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2022)
The speech writing training was carried out because based on the author's observations, at the time of the halal bi halal event, PRN youths were still limited in their ability to compose a series of welcome remarks at that time. Each recitation youth did not dare to put himself forward to convey his words. This is due to the lack of training materials that support their skills in writing greetings. In order to overcome this gap, the community service team from the South Tapanuli Muhammadiyah University (UM Tapsel) offered to hold a speech writing training for PRN Aek Badak. The purpose of this service is so that PRNs are skilled in writing welcoming speeches and can become useful skills in society in every community activity. The method used is the provision of interactive material through power points and training in writing a systematic welcome. The results of this community service activity have shown that the ten participants have succeeded in writing their respective remarks well and systematically. Thus, this speech writing training can be classified as a useful training and has been implemented in accordance with expectations, namely to train the younger generation to be ready to appear in the community at any event, anytime, and anywhere with pride.